Challenges, open innovation, and engagement theory at craft SMEs: Evidence from Indonesian batik - Alia Bihrajihant Raya; Riesma Andiani; Abi Pratiwa Siregar; Imade Yoga Prasada; Fairuz Indana; Theresia Gracia Yunindi Simbolon; Agustina Tri Kinasih; Agus Dwi Nugroho (Journal of Open Innovation: Technology, Market, and Complexity, 2021)
Indonesian batik small and medium enterprises (SMEs) are rapidly growing, but they face many challenges in developing their business. For this reason, we propose a combination of open innovation and engagement theory to overcome these challenges. We conducted interviews with 27 local government officers (external stakeholder) and 57 managers of batik SMEs (internal stakeholder). We confirmed the interview results with 20 batik experts and representatives from the Indonesian Ministry of Industry in the Focus Group Discussion. We have divided the findings of this study into two categories: Java and outside of Java, since the two areas have different characteristics. According to our findings, the biggest challenge of batik SMEs in Java is the emergence of the batik printing business. Meanwhile, batik SMEs outside of Java are having difficulty obtaining raw materials. Open innovation has been implemented by some batik SMEs in Indonesia and can improve their business performance. However, more batik SMEs do not implement open innovation due to the lack of their skills and involvement of other stakeholders. As a result, we suggest that open innovation in the Indonesian batik industry needs to be supported by the participation of various parties or that open innovation is combined with engagement theory.
Keywords: 650; challenges; open innovation; participation; performance; stakeholders